2005
DOI: 10.1302/0301-620x.87b9.15972
|View full text |Cite
|
Sign up to set email alerts
|

Patellar height and the inclination of the tibial plateau after high tibial osteotomy

Abstract: Our aim was to compare the degree of patellar descent and alteration in angle of the inclination of the tibial plateau in lateral closing-wedge and medial opening-wedge high tibial osteotomy (HTO) in 51 consecutive patients with osteoarthritis of the medial compartment and varus malalignment. Patellar height was measured by the Insall-Salvati (IS) and the Blackburne-Peel (BP) ratios. The tibial inclination was determined by the Moore-Harvey (MH) method. Multivariate linear regression analysis was used to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
175
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(203 citation statements)
references
References 16 publications
15
175
3
1
Order By: Relevance
“…To some extent, our study showed a similar distribution of patellae norma, alta and infera as reported in the literature at the site of different surgical indications [12,[30][31][32]. In some cases, our results demonstrated great variations in the determined values.…”
Section: Discussionsupporting
confidence: 87%
“…To some extent, our study showed a similar distribution of patellae norma, alta and infera as reported in the literature at the site of different surgical indications [12,[30][31][32]. In some cases, our results demonstrated great variations in the determined values.…”
Section: Discussionsupporting
confidence: 87%
“…Depending on the surgical technique and postoperative management, alterations in patellar height can be induced [2,3,6,11,14,16,21]. Open wedge osteotomy (OWO) proximal to the tibial tuberosity, which is gaining popularity in recent years, has been reported to cause patella baja [6,12,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the traditional osteotomy techniques also create alignment changes in the sagittal plane, which can adversely affect knee biomechanics and kinematics. Closing wedge osteotomies have been shown to decrease posterior tibial slope [25][26][27], whereas opening wedge osteotomies cause an increase in posterior tibial slope [25,28]. These changes can adversely affect postsurgical outcomes in patients with concomitant ligamentous laxity or patients that eventually require arthroplasty.…”
Section: Introductionmentioning
confidence: 99%